The leadership role in healthcare management - Lopes da Costa, R.; Pereira, R. da C.; Pereira, L.; Dias, Á.; Gonçalves, R.; Carrachás, E. (International Journal of Economics and Business Research, 2022)
Within the changes in the Portuguese healthcare system across the years, new challenges emerge for healthcare practitioners, organisations, and their management boards, so the recognition of the need for different health professionals in healthcare management has been growing. However, physiotherapists’ core responsibilities remain rooted on therapeutic practices and rehabilitation, developed primarily in clinical and hospital environments. Regarding this scenario, physiotherapists’ functions continue to be absent to the highest healthcare management and leadership positions, despite their knowledge and understanding about how to ensure the best services to the patients. Using a mixed method approach, this investigation aimed to deepen the drivers to physiotherapists’ involvement in healthcare management and leadership roles. For such, we combined a cross-sectional survey was performed with 287 physiotherapists with in-depth interviews. Findings suggest that networking, knowledge regarding health legislation and policies, and soft skills development, are considered drivers to these roles, amongst other factors.